The Literal and the Literary: A Note on the Historical References in Isabel Allende's La casa de los espíritus - Scott Macdonald Frame (Studies in 20th & 21st Century Literature, 2003)
Stripped of much of its individuality as a piece of literature and relegated to the niche set aside for women's writing, Isabel Allende's La casa de los espíritus has sometimes wrongfully been critically condemned as a mere facsimile of García Màrquez's seminal Latin American novel. However, if critics were to reexamine La casa de los espíritus as a work of fiction in which its writer attempts to give voice to, and achieve personal closure of, historical events so tragically real for her, its comparisons with that "other" Latin American novel might be less frequent. This article contends that Allende uses a mixture of traceable historical facts, unsubstantiated personal accounts, and urban myths perpetuated by popular hearsay to present a plausible version of what could have happened during the events surrounding the fall of Salvador Allende on September 11, 1973. The crux of the argument presented will be that by superimposing unsubstantiated or distorted fact and local myth, Allende calls into play an understanding of traceable historical referents and creates a sense of associative identification between the reader and the text and the characters within. This reconstituted image provides a reinterpretation of what happened, a plausible scenario by means of which one can negotiate or interpret the varying shades of "truth" associated with the events as they may have occurred. This article further argues that through the use of familiar and identifiable images of a closer-to-the-fact fictionalization of real historical incidences, Allende is able to create a more credible characterization and historicity in the novel as well as sensitise her target reader to the resultant social and political changes of what many of her countrymen consider the single most fateful day in their nation's history.
Keywords: Isabel Allende; la case de los espíritus; historical fiction; Salvador Allende; myth; truth; social change; political change